Coniella castanea sp. nov. on Castanea mollissima from Shandong Province, China - Wang, Shi; Mu, Tai-Chang; Liu, Rong-Yu; Liu, Shu-Bin; Zhang, Zhao-Xue; Xia, Ji-Wen; Li, Zhuang; Zhang, Xiu-Guo (Phytotaxa, 2022)
Coniella has a wide distribution as plant pathogens, saprobes and endophytes. Some Coniella species infect leaves, fruits, stems and roots of plants. A coniella-like species was isolated from symptomatic leaves of Castanea mollissima (Fagaceae) from orchard in Tai’an City, Shandong Province, China. Based on multi-locus phylogenetic analyses of ITS, LSU, RPB2 and TEF1-α sequence data and morphology, Coniella castanea sp. nov. is introduced. A detailed description and illustration has been provided and new specieswas compared with related taxa.